Green Technology Adoption: A Systematic Review of Key Trends and Challenges - Cahyadi, Dede; Widya, Tilly Raycitra; Christanto, Duta Arief; Nasrullah, Muhammad Hudzaifah; Giantri, Lilik Tiara (Journal of Applied Informatics and Computing, 2025)
This study systematically reviews the trends, drivers, and barriers of green technology adoption, synthesizing insights from 81 articles indexed in the Scopus database from 2019 to 2025. Employing the PRISMA framework and bibliometric analysis, the research aims to provide a comprehensive overview of the academic landscape and offer evidence-based guidance for stakeholders. The findings reveal a growing, albeit limited, academic interest, with a research peak in 2024. Geographically, the discourse is led by developed nations and emerging economies, notably China, while research predominantly focuses on high-impact sectors such as transportation, energy, and manufacturing, leaving critical sectors like agriculture under-examined. Furthermore, this review provides a theoretical contribution by mapping empirical findings onto the Green Innovation Cycle and the Stimulus-Organism-Response (S-O-R) model, thereby strengthening the explanatory power of existing frameworks. We identify key challenges spanning infrastructure, policy, and user behavior, and provide specific recommendations for policymakers, industry leaders, and researchers to foster a more equitable and effective green transition. This research serves as a robust scientific foundation for future studies and strategic initiatives to accelerate global green technology adoption.